Implementation of 288 KWP Photovoltaic Solar System On-Grid in a Manaus Industrial Polo Company - Oliveira, Ítalo Pedro Santos de; da Silva Oliveira, Livia; Barbosa de Alencar, David; Reis Nascimento, Manoel Henrique (International Journal for Innovation Education and Research, 2019)
The rational use of electricity is practically mandatory, due to the current moment in which the country crosses, mainly due to the reduced reservoir levels of the hydroelectric plants, and where there are high costs in the production of its fuel inputs. fossil fuels, and recent tariff adjustments that the government has been approving year after year, making conventional energy increasingly expensive in the country. Companies and households focus on looking for ways to dodge electricity inflation through clean and renewable energy sources, as is the case here, of photovoltaic solar energy. Aiming to supply about 70% of the electricity bill of a Company of the Manaus-AM Industrial Pole, this work proposes a 288 KWp photovoltaic solar system, consisting of 900 330 W photovoltaic panels, accompanied by 10 Inverters. 30 KW each, connected to the Amazonas Energia Distribution Network, featuring an On-grid solar system, and becoming the largest executed solar energy project in the Amazon and Northern Brazil. The implementation of the system seeks to make feasible and solve the high cost of the electric bill with the application of a solar system, and analyze its investment, financial return and clean energy generation for the next 25 years.